CHILD PROTECTION IN THE FATWA OF MUHAMMADIYAH COUNCIL FOR RELIGIOUS OPINION AND TAJDID IN 2024 AND LAW NO. 35 OF 2014 - Efendy, Imam Nur; Ikhwanuddin, Mohammad; Al Farisi, Salman; Stiawan, Thoat; Berkah, Dian (Universitas Islam Negeri Mataram, 2025)
This study analyzes the protection of children's rights from a comparative perspective between the Fatwa of the Muhammadiyah Tarjih and Tajdid Council Number 54/KEP/I.0/B/2024 concerning Child Protection Jurisprudence (Fiqh) and the Law of the Republic of Indonesia Number 35 of 2014 concerning Child Protection. The research problem focuses on the similarities and differences in the legal substance between the aforementioned Fatwa and the Child Protection Law in terms of guaranteeing children's rights. Both legal sources share four main similarities: the right to life and development, the right to education, the right to custody (hadanah), and the right to express an opinion. However, there are three main differences: (1) the legal sources used, where the Fatwa is derived from Islamic teachings, while the law is based on state law; (2) the Fatwa does not directly address the rights of children with disabilities, although attention to this issue is contained in a separate Fiqh for Disabilities; and (3) (Assumption: Insert the third explicit difference if available in the original text, or focus on implications). This research used a qualitative method with a juridical-normative approach, analyzing relevant documents and literature. The results indicate that significant issues remain to require attention, such as the lack of clear regulations for child protection in the digital age, the continued occurrence of child marriage despite its prohibition, and the limited space for children to express their opinions due to authoritarian family cultures. This research recommends the importance of incorporating religious values into state policy and the need for further study on the protection of children with disabilities and children in the digital world from an Islamic perspective.